Analisis Destruction Test Tower Sutet dibandingkan dengan Software Ms Tower dan SAP 2000 - Eko Bayu Aji; Johannes Tarigan; Emma Patricia Bangun (Syntax Corporation Indonesia, 2023)
The transmission line system which is currently growing rapidly in Sumatra, requires a reliable interconnection network to meet the electricity demand for the West Sumatra region. PT. PLN as a provider of electricity businesses in Indonesia conducted planning and destruction tests to design a new model Extra High Voltage Transmission Line (SUTET) tower with specification of 66.6 meters height, slim type tower, 275 kV, lattice BB+15, quadrapole zebra (435/55 mm2) 2 cct. This research aims to study tower collapse behavior caused by working loads, analyze and compare the suitability level of tower deformation and natural frequency among MS Tower, SAP 2000 space truss analysis, SAP 2000 space frame analysis with destruction test results. SAP 2000 space frame deformation analysis shows that the tower is unstable in the Leg section. The analysis of natural frequency and the mode shape in the SAP 2000 space frame analysis is close to the value of the natural frequency destruction test with a deviation of 30%. The tower collapse occurred due to imperfection geometry on the legs section, resulting in a global collapse. Improvements in the form of adding equal angle to the hip bracing were carried out, the result was able to withstand a load case load of 9870 up to 100%. Space frame analysis on SAP 2000 is closer to MS Tower, this can be seen from the deformation and natural frequency values that approach each other from the two analyses.